The Analysis of Junior High School Students' Misconceptions Using Five-Tier Diagnostic Test in The Concept of Living Things Classification - Amalia, Dila; Fikriyah, Aida; Tamam, Badrud; Sidik, Rahmad Fajar; Wulandari, Ana Yuniasti Retno (Fakultas Tarbiyah dan Ilmu Keguruan, UIN Kiai Haji Achmad Siddiq Jember, 2023)
This research aims to describe the percentage of misconception levels of junior high school students using a five tier diagnostic test on the classification of living things. This type of research is quantitative descriptive with a population of class VII students at SMP Negeri 3 Bangkalan for the 2022/2023 academic year. The samples used in the research were classes VII-A and VII-D based on purposive sampling techniques. Data collection was carried out by administering five tier diagnostic test questions. The research results showed that: 1) Students experienced M (Misconception) 37.73%, SC (Scientific Conception) 17.27%, ASC (Almost Scientific Conception) 2.73%, LK (Lack of Knowledge) 26.64%, NU (No Understanding Conception) 15.18%, and UnC (Un-Code) 0.45%, 2) The percentage of classification of misconception levels based on calculations using standard deviation and the mean of students is in the low misconception category of 27.27%, moderate misconception amounted to 52.73%, and high misconceptions amounted to 20%. Based on the results of the research and data analysis carried out, it can be concluded that the high percentage of students' misconceptions indicates that the material on the classification of living things is quite difficult for students at SMP Negeri 3 Bangkalan to understand.